Subject Matter and Pre-Requisites for Protection of Non-Conventional Trademark - Vatsa, Aishwarya (Christ University Law Journal, 2019)
We have been gifted with senses other than our eyes, which the non-conventional trademarks aim to employ and have thus gained popularity. These marks have gradually acquired acceptance and have been included under the ambit of trademarks in various countries of the world. Trademark law aims at facilitating profit and strengthening the identity of a business. Non-conventional marks too, perform the same function. The United States has taken a similar approach and has thus provided protection to various such non-conventional marks. India, on the other hand, is yet to take a similar approach. The present law in India disallows the registration of such marks, proving to be a hindrance in their registration, rather than a facilitator. This paper discusses the concept and definition of non-conventional marks, its subject matter and the prerequisites for its registration. By comparing the different approaches to non-conventional trademarks and the procedure for their registration across different countries, this paper aims at suggesting a model suitable for adoption in India.